Dinámicas grupales como estrategia didáctica para el desarrollo de la autoestima en los estudiantes de quinto y sexto año de la escuela de educación básica Mons. Juan María Riofrío. Periodo 2018-2019. - Medina Barrera, Monica Yaritza (2019)
Self-esteem is a fundamental aspect in the integral development of children, therefore, the low level of it brings with it innumerable negative consequences both in childhood and in adulthood if it is not addressed in time. Therefore, the research topic called GROUP DYNAMICS AS A DIDACTIC STRATEGY FOR THE DEVELOPMENT OF SELFESTEEM IN STUDENTS OF FIFTH AND SIXTH YEARS OF THE BASIC EDUCATION SCHOOL MONS. JUAN MARÍA RIOFRÍO. PERIOD 2018-2019. With the general objective of employing group dynamics as a didactic strategy for the development of self-esteem in the fifth and sixth year students of the School of Basic Education Mons. Juan María Riofrío. The investigation corresponded to a descriptive, pre-experimental and cross-sectional study. The methods Investigation - action (AI), scientific, deductive - inductive and analytical - synthetic were used; The psychological reagent consisted of César Ruíz Alva's self-esteem test, which was applied to a population of 51 fifth and sixth year students, the main results showed a low level of self-esteem and after the application of the alternative proposal through. The workshops show a highly significant change. From which it can be concluded that the group dynamics used gave positive results; so I recommend to the directors of the institution to continue with its application.